Anti-urolithiatic terpenoid compound from plantago major linn. (Ekor Anjing)(Aktiviti anti-urolitiatik sebatian “terpenoid” daripada Plantago major Linn. (Ekor Anjing)) - Sharifa, A.A; Jamaludin, J; Kiong, L.S; Chia, L.A; Osman, K (Universiti Kebangsaan Malaysia, 2012)
The aim of this study was to determine the inhibition effects of the terpenoid of Plantago major on calcium oxalate crystals in vitro and to compare the effects of Plantago major with clinically used drugs like zyloric and potassium citrate for the treatment of urinary stone. Modified Schneider slide gel method was used for in vitro study and crystals formed were measured by Image Analyser System (Leica) after 24 h of treatment. The active compound in the methanol extract of Plantago major was isolated by bioassay - guided fractionation & isolation method. Dimethylsulphoxide (DMSO) was used as the negative control and zyloric and potassium citrate were used as positive controls. The results showed that crude methanol extract of Plantago major contained the active compound terpenoid. Terpenoid, zyloric and potassium citrate at concentrations in the range of (100 μg/ml - 250 μg/ml) significantly inhibited the area of crystal formation in comparison to the negative control after 24 h (p<0.001). The Zyloric and terpenoid of Plantago major in the concentrations of (100 μg/mL-250 μg/mL) inhibited the sizes of crystals significantly (p<0.05). Potassium citrate was more effective, than terpenoid of Plantago major in inhibiting the size of crystals at two concentrations i.e 100 μg/mL and 150 μg/mL respectively (p< 0.05). However the IC50 values for terpenoid of Plantago major, potassium citrate and zyloric were 250 μg/mL, 300 μg/mL and 550 μg/mL, respectively. The inhibition effect of the terpenoid of Plantago major extract on crystal size was much better than Zyloric and potassium citrate.